The Scope of the Philosophy of Science: A Review of Philosophical Education - Hambali, Adang; Herniawati, Ani; Hidayat, Yusuf (CV. Tripe Konsultan, 2024)
The philosophy of science is a branch of philosophy that discusses the nature of science. The philosophy of science attempts to realize the true truth of the knowledge. This article aims to discuss the scope of the philosophy of science which consists of definition of philosophy, definition of the philosophy of science, characteristics of philosophical thoughts, and three fundamental structures of science. In this study, the researchers employ qualitative method under descriptive approach. Meanwhile, in the present study the researchers used content analysis as the data analysis technique. The results showed that philosophy is a way of humans’ thoughts in relation to the study of the fundamental and eternal universe. Furthermore, when philosophy is connected into science, it becomes the philosophy of science. The philosophy of science then is understood as a part of philosophy whose activities to examine science in the context of science through various scientific procedures including initial principles, theoretical structures, measures of scientific truth, views of formal logic, and practical methodology and metaphysics. In addition, philosophy is inseparable from the characteristics of philosophical thoughts which consists of methodical, systematic, coherent and consistent, rational, comprehensive, radical, and univesal. Finally, philosophy examines three aspects of the fundamental structure of science including aspect of ontology, epistemology, axiology. In conclusion, the philosophy of science has four scopes including definition of philosophy, definition of the philosophy of science, characteristics of philosophical thoughts, and three fundamental structures of science.